(3SOQI GdefJgis - (3GHf hMTjI , CMeO Hf Ydj Hf bjS Hf GdeNJGQ Hf YHO GdcQje Hf MQKjG, CHh HcQ,J (B291 (3g` s
(3ChdgG (B:s
(3bGd de JQc GdMceGA ef GdCee GdSGdaI hGdbQhf GdNGdjI jMJGdhf ai EXgGQ Mcege hJbhjI eG jQhf s
(3BNQgG (B:s
(3dhLhO Pdc GdTF ajg GdPi jdhf efg gPG GdCcSjQ GdLdjd hgPG BNQ GdcdGe JMQ gPG GdcJGH GdeHGQc GdeSei HSOQI GdefJgi s
(3HChdg hCNQg fbhds
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B170 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B23s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdcjejGA h GdWHjYjGJs